Internalization of Anti-Corruption Character Values Through Pancasila Education Learning - Yunarti, Azmi; Perdana, Gusti Muhammad Raja Putra; Saufi, Muhammad; Iedliany, Faradilla (Electronic Journal of Education, Social Economics and Technology, 2024)
Personality is a characteristic, characteristic, or distinctive trait possessed by a person that originates from the formations received from the surrounding environment, namely the family that begins from childhood and is innate since birth. Character education provided from an early age is the right step to produce an anti-corruption attitude, such as an honest, religious, and independent character so as to encourage elementary school students to stay away from and prevent corruption. Corruption is a very cruel crime, because it has robbed the rights of the community, especially those aimed at realizing public welfare. Criminal acts of corruption can only be committed by certain individuals, who generally have power and influence and in fact corruption has damaged the morality of the nation and has the potential to bring the Indonesian nation to the brink of destruction. So it is our obligation as citizens to save this nation, by practicing and socializing anti-corruption behavior from an early age. There needs to be theoretical confirmation through the results of academic endeavors, in order to provide argumentative information. Especially in the rationalization of Pancasila Education which is very competent to be optimized as anti-corruption education. How is the internalization of anti-corruption character values in Pancasila Education learning? Data collection was carried out using several techniques, namely interviews with respondents and literature studies to trace document data. The data obtained was then processed by first checking its validity in order to obtain data that could be accounted for and scientific. Data processing techniques include data collection, data reduction, data presentation, and drawing conclusions. Instilling anti-corruption character values is an important component in Pancasila learning. The implementation of anti-corruption character values should be carried out early on. Efforts to internalize anti-corruption character values need support from parents in guiding their children to apply character values while at home.